2009
DOI: 10.1073/pnas.0900711106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depth on mercury levels in pelagic fishes and their prey

Abstract: Mercury distribution in the oceans is controlled by complex biogeochemical cycles, resulting in retention of trace amounts of this metal in plants and animals. Inter-and intra-specific variations in mercury levels of predatory pelagic fish have been previously linked to size, age, trophic position, physical and chemical environmental parameters, and location of capture; however, considerable variation remains unexplained. In this paper, we focus on differences in ecology, depth of occurrence, and total mercury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
144
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 50 publications
13
144
2
Order By: Relevance
“…In the ocean Hg primarily exists as inorganic Hg(ii) or Hg (0) [5][6][7] . In agreement with these vertical profiles, total Hg (THg) levels in commercially important predatory pelagic fish and their prey increase with median depth of occurrence 8,9 , which is indicative of both foraging depth and habitat utilization. However, the biogeochemical factors controlling the distribution and speciation of Hg in the ocean and the bioaccumulation of MMHg in marine food webs are still not well understood 10 .…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…In the ocean Hg primarily exists as inorganic Hg(ii) or Hg (0) [5][6][7] . In agreement with these vertical profiles, total Hg (THg) levels in commercially important predatory pelagic fish and their prey increase with median depth of occurrence 8,9 , which is indicative of both foraging depth and habitat utilization. However, the biogeochemical factors controlling the distribution and speciation of Hg in the ocean and the bioaccumulation of MMHg in marine food webs are still not well understood 10 .…”
mentioning
confidence: 62%
“…We analysed samples of muscle tissue from either three or four individuals from each of nine species of fish (six high-TP predatory species, three low-TP prey species; Supplementary Table S1 for species names and data on core depth ranges and median depths of occurrence) collected in the central NPSG near Hawaii and previously analysed for THg concentrations 8 . Electronic tagging and trawling studies provide very useful information on vertical habitat utilization.…”
Section: Species Sampled and Their Depth Of Occurrencementioning
confidence: 99%
See 2 more Smart Citations
“…KANNAN et al (1998) found high values of methylmercury in striped weakfish off southern Florida, four times higher than those occurring on the Cabo Frio Coast, demonstrating the important role of this species in the mercury transfer studies of Atlantic Ocean fish. CHOY et al (2009) observed that demersal carnivorous species present a greater tendency to incorporate mercury than do the pelagic ones. This is attributed to the greater mercury availability at the water-sediment interface due to the methylation processes that occur in this system.…”
Section: Methodsmentioning
confidence: 99%